-5(4y-2)-y=-4(y-2)

Simple and best practice solution for -5(4y-2)-y=-4(y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(4y-2)-y=-4(y-2) equation:


Simplifying
-5(4y + -2) + -1y = -4(y + -2)

Reorder the terms:
-5(-2 + 4y) + -1y = -4(y + -2)
(-2 * -5 + 4y * -5) + -1y = -4(y + -2)
(10 + -20y) + -1y = -4(y + -2)

Combine like terms: -20y + -1y = -21y
10 + -21y = -4(y + -2)

Reorder the terms:
10 + -21y = -4(-2 + y)
10 + -21y = (-2 * -4 + y * -4)
10 + -21y = (8 + -4y)

Solving
10 + -21y = 8 + -4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4y' to each side of the equation.
10 + -21y + 4y = 8 + -4y + 4y

Combine like terms: -21y + 4y = -17y
10 + -17y = 8 + -4y + 4y

Combine like terms: -4y + 4y = 0
10 + -17y = 8 + 0
10 + -17y = 8

Add '-10' to each side of the equation.
10 + -10 + -17y = 8 + -10

Combine like terms: 10 + -10 = 0
0 + -17y = 8 + -10
-17y = 8 + -10

Combine like terms: 8 + -10 = -2
-17y = -2

Divide each side by '-17'.
y = 0.1176470588

Simplifying
y = 0.1176470588

See similar equations:

| 6n+3n+3120=5400 | | -6+-1y=10 | | -7p-4=2p+40 | | 17=102 | | 6+-1y=10 | | 2(3s+2)=76 | | -4.9m^2+34.3m+0=58.8 | | 10(2x-11)=90x | | 2x+Y+4z=19 | | 12=15-9(3) | | 4x+2x-x= | | 13+(29+7)=13+(7+29) | | -5(x+3)=-14-4x | | R=4x+12 | | 3-(3x-6)=2+5x | | C(m)=0.5m+25 | | 5(2l+7)=55 | | 6z^2+7z+2=0 | | 9(x-2)=-3x+78 | | R=5x-16 | | .5555(9x+12)=10 | | 4-7(1-2v)=-33+8v | | p^2=2p+8 | | -x-2=-12 | | -30-5n=6(n+4) | | -9=117 | | .64x^2-6x-5000=0 | | 3(7X+8)=2(2x-4) | | p+3=80 | | -3x+9=6x+81 | | 3(3m-2)=3(m+3) | | 17x-(3x-6)=34 |

Equations solver categories